MAQĀṢID AL-SYARĪ'AH'S REVIEW OF THE MARKETING OF MEAT OF ANIMALS THAT DO NOT HAVE A SLAUGHTER PERMIT FROM AN ANIMAL HEALTH CLINIC IN ACEH BESAR REGENCY - Salsabila, Puja; shabarullah (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2025)
This study examines the review of maqāṣid al-sharī'ah on the marketing practices of animal meat that lack a slaughter permit from an animal health clinic in Aceh Besar Regency. In practice, there are still meat traders who market animal meat without obtaining an inspection and slaughter permit from an animal health doctor at the Slaughterhouse (RPH), especially at certain times, such as during the meugang period. This study aims to analyze the marketing pattern of animal meat in Aceh Besar and assess its conformity with the principles of maqāṣid al-syarī'ah. This research is empirical legal research (field legal research) with a socio-legal and conceptual approach. Data were obtained through interviews and literature studies, which were then analyzed descriptively and prescriptively. The results of the study show that the marketing of animal meat in general has been under the supervision of animal health clinics. However, the supervision does not run optimally on certain days, thus allowing the circulation of animal meat that is not fit for consumption. The practice of marketing meat without a slaughter permit is not in line with maqāṣid al-syarī'ah because it has the potential to cause maḍarrah and is contrary to the purpose of Islamic law in safeguarding the benefit of the community.